La experiencia de morir : reflexiones sobre el duelo anticipado (2011)
ABSTRACT: This article offers some reflections on the experiences of terminally-ill patients, in order to explain the peculiarities of the anticipatory mourning that persons declared incurable by medical science. Three theoretical perspectives on this issue are used to support the point of view of the authors concerning hat in this type of mourning, the object is life itself. On the basis of clinical experience and of the literature, the article also shows how this psychic phenomenon that the incurable person experiences can express itself in two opposite ways: to die suffering or live to the very end.